History of human emotions as a specific field of research - URSU, Miluta (Acta et Commentationes, Sciences of Education, 2026)
The proposed study addresses the history of human emotions, outlined as a potential new discipline within psychology. The issue is examined through three perspectives on emotional intelligence: as closely related to interpersonal and intrapersonal intelligences; as distinct from intelligences predominantly based on cognitive processes; and as a factor directly and indirectly involved in the development of any activity. Considered a scientific discipline, the history of emotions studies the evolution of affective states within community, cultural, and historical contexts, using specific methodologies and concepts such as emotional regimes and emotional communities. It traces the transformations of emotions from Antiquity to the present, including in relation to new technologies, without reducing the complexity of human experiences.